The Influence of Trust on Creativity: A Review - Chen, Yan; Yu, Cheng; Yuan, Yuan; Lu, Fang; Shen, Wangbing (Frontiers in Psychology, 2021)
Examining the trust-creativity relationship is important to promote creativity and organizational innovation. The purpose of this study is to examine how trust influences creativity by reviewing empirical findings across diverse studies. The impact of trust across different levels on creativity is primarily manifested in three ways: (1) individuals’ cognition-based and affect-based trust have a positive effect on creativity together with the role of trust-derived perspective-taking in creativity; (2) interpersonal trust helps to boost the joint creativity of the entire group via mediators such as team communication and commitment together with trust-evoked safety and the motivation to risk proposing, sharing, accepting or adopting uncommon ideas; (3) group trust has a positive, mostly indirect effect on creativity via mediating variables such as collaborative culture or climate and team communication. Potential implications and future directions are also discussed.